Creación de una agencia de asistencia técnica para la ciudad de Guayaquil, donde se ofrecerán trabajos de reparaciones domésticas garantizadas a domicilio para la ciudad de Guayaquil - Montalvo Chalen, Monica (2009)
The prospect of the Sector Services in our country is encouraging, although its contribution level to the economy still smaller than in industrialized countries (between 66% and 80%), while in our country it is around 50%. The perception that this sector ls growing is reflected in the Managerial Confidential lndex (M'Cl) ofthis sector in the Guayas County, it is increased in 16.4 points in August of the 2008 with relationship a month ofJuly, determining that the MCl aggregale ofthe sector ascends lo 328.0 points, according lo statistical ofthe Central Bank.Contrarytothemessaging andcleaningservicesthatarearrivinglotheendof demandcovering,theofferof repairs and technical support to home it is not still completely exploited, since they are few companies that offer it in a guaranteed way, being the main carried out offer in an informal wuy in the streets ofour city therefore there are a unsatisjied demand that is the one that the project aims to arrive